BUSINESS JUDGMENT RULE - EXONERATION OF LIABILITY CAUSE OF THE ADMINISTRATOR. COMPARATIVE LAW STUDY - CARMEN TODICA (Challenges of the Knowledge Society)
Starting from the origin system- the American law, and from the principles of corporate governance which establishes it expressly, the study reveals the regulatory manner in Company law and also the implication of legal practice, of the “business judgment” rule. Seen from a double perspective: as a ground for exclusion of liability clause from civil liability of the administrator, but also as a counterweight to the diligence and prudence duty, the business judgment rule is analyzed in accordance with the legal liability falling within the administrator’s duties, both by Law no.31/1990 and the New Civil Code. Discussing also by the standard for appreciating the prudence and diligence- the criterion of the good administrator- imposed by the Romanian legislation, compared with other countries, the paper approaches the manner for regulating the business judgment rule in American law, and the manner in which it has been transposed into the Romanian legislation, its application realm, the invocation method and the consequences of this rule on the civil liability of the administrator. This paper constantly refers to the legal practice solutions in common-law states, where the rule stems.